Welcoming cheeky children into the conference hall: Morss, J R (1997) Growing critical: Alternatives to developmental psychology. London: Routledge. ISBN 0-415-06109-1 - Jackson, Carey-Ann (PINS-Psychology in Society, 2026)
Constructing a bounded space within which it is possible to differentiate South African developmental psychology from any other strand of developmental psychology is neither an easy nor an intellectually trendy thing to do. But for the purposes of this review, I will ask that the reader momentarily excuse my impudence I have constructed a boundary around South African developmental psychology because I believe that we are distinctive for one main reason. South African developmental psychology is unable to reconcile problems of explanation and intervention (confronting us in the heterogeneous settings within which we work) with the theoretical models that emphasise the inappropriateness of the developmental paradigm. In a word, South African developmental psychology is uncritical. I could suggest several reasons for this but for the sake of this review, I will point out only one. We have come to rely too heavily on mostly US-published reference materials such as textbooks and journals that are static, dry and overwhelmingly uncritical. Growing critical may be the alternative we need to challenge our views of development and developmental psychology.